A Review on Surface Characterization Techniques of Polymeric Membrane in Forward Osmosis. Issue 5 (January 2020) - Aziz, Siti N. S. A.; Seman, Mazrul N. A.; Saufi, Syed M.
Abstract: Forward osmosis (FO) is an emerging osmotic process that has been extensively investigated in the past decade. There are many literatures, discussing on the available methods in producing FO membranes as well as researches that emphasis on the type of FO membranes. The quality of the FO membrane often valued based on its intrinsic parameters and its morphological characteristics. Unlike the intrinsic parameters, the surface characteristics regularly described in adjectives thus it is hardly to be consistent. This paper presents a comprehensive review on surface characterization specifically for FO membranes. Regardless the types of FO membranes, the surface characterization comprises of FTIR, XPS, FESEM/SEM, AFM and contact angle were discussed in the way that how the findings should be reported. Thus, through this work, the relevant discussion that should be measured and included when deliberating the analysis result for FO membranes is presented. Insufficient and misinterpreted characterization data might have not changed the novelty fact of the research, yet it may lead to lower its impact. A strong connection between the intrinsic values and surface characteristics would have been compromised as well.